Electromyography varies by stage in inclusion body myositis - Mano, Tomoo; Iguchi, Naohiko; Eura, Nobuyuki; Iwasa, Naoki; Yamada, Nanami; Horikawa, Hirosei; Sugie, Kazuma (Frontiers in Neurology, 2024)
Introduction Inclusion body myositis (IBM) is a chronic inflammatory muscle disease that is characterized by mixed myogenic and neurogenic electromyography (EMG) findings. We investigated the association between EMG findings and the IBM stage. Methods We included consecutive patients diagnosed with IBM based on muscle biopsy and had needle EMG performed within 1 month of biopsy. Motor unit potential waveform (MUP) in EMG and pathological findings were compared between patients in early and late phases. Results In total, 30 patients with biopsy-confirmed IBM and 254 muscles were included. The rate of abnormal discharge did not differ according to disease stage. There was a difference in the frequency of occurrence between myogenic suggestive MUP and neurogenic of biceps and flexor digitorum profundus in the late phase. Abnormal MUP was observed even in muscles without muscle weakness, and myogenic changes were predominant in biceps and gastrocnemius with muscle weakness. The biopsy findings on the contralateral side of the muscle where electromyography was performed revealed a tendency for muscles that exhibited myogenic origin to have more inflammatory cells and RV; however, the difference was not significant. Conclusion The target muscles for EMG must be selected considering the disease stage as well. In the early stages of IBM, EMG results should be interpreted cautiously, as neurogenic suggestive pattern of MUP might also be exhibited. Contralateral electromyography findings may be helpful in selecting muscles for muscle biopsies, such as biceps and quadriceps.